2009
DOI: 10.1007/s00535-009-0108-9
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic transpapillary intraductal ultrasonography and biopsy in the diagnosis of IgG4-related sclerosing cholangitis

Abstract: The IDUS findings were useful for distinction of IgG4-SC from cholangiocarcinoma. Transpapillary biopsy was not useful for direct diagnosis of IgG4-SC even after IgG4 immunostaining, but it did allow distinction of IgG4-SC from cholangiocarcinoma in some cases. IDUS and transpapillary biopsy after endoscopic retrograde cholangiopancreatography can provide further information for precise diagnosis of IgG4-SC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
152
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 151 publications
(165 citation statements)
references
References 19 publications
9
152
2
2
Order By: Relevance
“…7,8 Naitoh et al reported that lower bile duct strictures appeared as marked wall thickening in 93% of patients, and as extrinsic compression in 7% of patients, revealing lower bile duct stricture caused mostly by bile duct wall thickening. 12 Other 14 studies also support that lower bile duct stricture in AIP is due to inflammatory processes in the bile duct. 20,21 Pathological studies of resected tissue specimens from the pancreatic head revealed abundant lymphoplasmacytic and IgG4-bearing plasma cell infiltration not only in pancreatic tissue, but also in the bile duct wall, indicating that the lower bile duct stricture lesion was due to IgG4-related inflammatory processes in the lower bile duct.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…7,8 Naitoh et al reported that lower bile duct strictures appeared as marked wall thickening in 93% of patients, and as extrinsic compression in 7% of patients, revealing lower bile duct stricture caused mostly by bile duct wall thickening. 12 Other 14 studies also support that lower bile duct stricture in AIP is due to inflammatory processes in the bile duct. 20,21 Pathological studies of resected tissue specimens from the pancreatic head revealed abundant lymphoplasmacytic and IgG4-bearing plasma cell infiltration not only in pancreatic tissue, but also in the bile duct wall, indicating that the lower bile duct stricture lesion was due to IgG4-related inflammatory processes in the lower bile duct.…”
Section: Discussionmentioning
confidence: 91%
“…Because IDUS showed continuous wall thickening from the lower to middle bile ducts, IgG4-related inflammatory changes in the bile duct seem to extend from the lower to middle bile duct in most cases even though cholangiography showed normal findings. 12 Middle bile duct stricture co-occurred with lower bile duct stricture in cholangiography for 4 cases. Thus, stenotic change in 4 middle bile duct cases appeared to share a common mechanism of IgG4-related biliary wall inflammation with lower bile duct stricture, suggesting that simultaneous lower bile duct stricture and middle bile duct stricture represents dominant IgG4-related bile 16 duct inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations